Natural Plants Compounds as Modulators of Epithelial-to-Mesenchymal Transition - Avila-Carrasco, Lorena; Majano, Pedro; Sánchez-Toméro, José Antonio; Selgas, Rafael; López-Cabrera, Manuel; Aguilera, Abelardo; González Mateo, Guadalupe (Frontiers in Pharmacology, 2019)
Abstract. Epithelial to mesenchymal transition (EMT) is a self-regulated physiological process required for tissue repair that in non-controled conditions may lead to fibrosis, angiogenesis, loss of normal organ function or cancer. Although several molecular pathways involved in EMT regulation has been described, this process does not have any specific treatment. This article introduces a systematic review of effective natural plant compounds and their extract that modulates the pathological EMT or its deleterious effects through acting on different cellular signal transduction pathways both in vivo and in vitro. Thereby, cryptotanshinone, resveratrol, oxymatrine, ligustrazine, osthole, codonolactone, betanin, tannic acid, gentiopicroside, curcumin, genistein, paeoniflorin, gambogic acid and cinnamomum cassia extracts, inhibit EMT acting on TGF-β/smads signaling pathway. Gedunin, carnosol, celastrol, black rice anthocyanins, duchesnea indica, cordycepin and celastrus orbiculatus extract downregulate vimectin, fibronectin, and N-cadherin. Sulforaphane, luteolin, celastrol, curcumin, arctigenin inhibit β- catenin signaling pathway. Salvianolic acid-A and plumbagin block oxidative stress, while, honokiol, gallic acid, piperlongumine, brusatol and paeoniflorin inhibit EMT transcription factors such as SNAIL, TWIST and ZEB. Plectranthoic acid, resveratrol, genistein, baicalin, polyphyllin I, cairicoside E, luteolin, berberine, nimbolide, curcumin, withaferin-A, jatrophone, ginsenoside-Rb1, honokiol, parthenolide, phoyunnanin-E, epicatechin-3-gallate, gigantol, eupatolide, baicalin and baicalein and nitidine chloride inhibit EMT acting on other signaling pathways (SIRT1, p38 MAPK, NFAT1, SMAD, IL-6, STAT3, AQP5, notch 1, PI3K/Akt, Wnt/β- catenin, NF-kB, FAK/AKT, Hh). Despite the huge amount of preclinical data regarding EMT modulation by plants natural compounds, clinical translation is poor. Additionally, this review highlights some relevant examples of clinical trials using natural plant compound to modulate EMT and its deleterious effects. In overall, this opens up new therapeutic alternatives in cancer, inflammatory and fibrosing diseases through the control of EMT process.